Pyramidal-Shaped Residual Subretinal Fluid at Fovea After Intravitreal Injection of Perfluoro-n-Octane in Eyes With Fovea-Off Rhegmatogenous Retinal Detachment. Issue 11 (November 2016) - Iwase, Takeshi; Ra, Eimei; Asami, Tetsu; Yamamoto, Kentaro; Kaneko, Hiroki; Terasaki, Hiroko
Abstract : Supplemental Digital Content is Available in the Text.